COST EFFECTIVE MICROPROPAGATION OF POLYSCIASFRUTICOSA (L.) HARM. (International Association of Biologicals and Computational Digest, 2022)
Polysciasfruiticosa(L.) Harm is plant which belonging to Araliaceae family, also known as Ming Aralia. Micropropagation is a technique to develop hole plant from the part of the plant in In-vitro or controlled environmental conditions. The research work focused on the micropropagation of Polysciasfruticosa(L.) Harm. from the shoot apex of the plant. Here only the cytokinin was used for the production of whole plant and M. S. Media. Generally, in Micropropagation auxin is used for the rooting phase but in this research work only kinetin which was used for the better growth for rooting also. Mostly the plant producing rare flowers and propagated through cuttings. Here M. S. Media with one Kinetin hormone standardized for the successful production of the plant lets of Polysciasfruticosa (L.) Harm. with this technique within 60days we can produce no. of plantlets of Polysciasfruticosa (L.) Harm.
Keywords: Micropropagation, Polysciasfruticosa (L.) Harm., M. S. Media, Kinetin